Pengaruh Model Project Based Learning berbasis STEM pada Pembelajaran IPAS terhadap Kemampuan Berpikir Kritis Siswa Kelas V di SDN 4 Mataram - Windi Astiana; Khairun Nisa; Ibrahim (Mataram University, 2026)
This study aims to determine whether there is an effect of the implementation of the STEM-based Project Based Learning (PEM) model in science learning about ecosystem balance material on students' critical thinking skills. This study uses a quantitative approach with a quasi-experimental pre-test post-test design model. Data collection techniques consist of observation and testing, namely using observation sheets for learning implementation, observations of the success of the terrarium project, and a critical thinking ability test consisting of 8 essay-type questions that have met the validity and reliability tests. The total sample is 60 students from SDN 4 and SDN 27 Mataram with a sampling technique using a purposive sampling technique. Data analysis techniques include prerequisite tests, namely normality and homogeneity tests, and hypothesis testing. Based on the results of the Shapiro Wilk normality test, the sig. value is <0.05, so the data is not normally distributed. In the Levene homogeneity test, the sig. value is 0.01 <0.05, so the data has a non-homogeneous variance. Therefore, the hypothesis testing uses a non-parametric test because it does not meet the assumptions of normality and homogeneity with Mann-Whitney U with the result of a Sig (2-tailed) value of 0.00 which is <0.05 so that it means Ho is rejected and Ha is accepted. It is concluded that there is an influence of the application of the STEM project-based learning model in science learning on the critical thinking skills of fifth-grade students of SDN 4 Mataram.